Расчеты на сейсмостойкость блока узла замера расхода газа - Гонтаровский, Павел Петрович; Глядя, Алла Александровна; Гармаш, Наталия Григорьевна (Национальный технический университет "Харьковский политехнический институт", 2019)
С помощью разработанной на основе метода конечных элементов расчетной методики проведены исследования сейсмостойкости блока узла замера расхода газа на розжиг факельной системы при сейсмических нагрузках различной интенсивности, которые за-даются с помощью реальных и синтезированной акселерограмм. Все элементы конструкции моделируются произвольно ориентированными стержнями и сосредоточенными массами с моментами инерции, которые соединяются между собой абсолютно жестко или с помощью упруго-демпферных элементов. Пластинчатые части конструкции моделируются решетками из стержней, учитывающими податливость и инерционные свойства ее элементов. Результаты проведенных исследований показали, что конструкция сейсмостойкая и не будет разрушена при ее эксплуатации.

To study seismic resistance of the box for the metering unit of gas flow-rate required to ignite the flare system we used the calculation methods developed on the basis of the method of finite elements and the software designed to define the mode of deformation and the dynamics of structures for the three-dimensional statement. To construct the simulation model, we took into account all the elements that affect the strength and the efficiency of the real structure during possible earthquakes. Structure elements were simulated using the sets of arbitrary oriented rods and lumped masses with inertia moments and those rods were connected absolutely rigidly with each other and using also elastically damped elements. The rod elements with distributed parameters took into consideration all the types of deformations that occur during the vibrations. The plate components of the structure were simulated using the grids made of the rods taking into consideration the ductility and inertia properties of its elements. Lumped masses in the rod connections were used to take into account the masses of installed equipment, pipelines, etc. The seismic loading was simulated using alternating inertia forces transferred from the ground. The soil ductility was taken into account by the Winkler model. Computations were done for the sand and rock stone ground and for the fine-grained sand. Consideration was given to the seismic forces of a different intensity that are represented by three-component accelerograms. Synthesized and real accelerograms were analyzed. The obtained computation data showed that the structure of the box of the metering unit of gas flow rate is quakeproof and it won’t be destroyed during its operation.
Seismic design of the box for the gas flow-rate metering unit
Keywords: фундамент; сейсмограмма; напряженно-деформированное состояние; собственные частоты; foundation; seismogram; mode of deformation; natural frequencies